Mesenchymal Stem Cells and Cardiomyocytes Interplay to Prevent Myocardial Hypertrophy. (19th November 2015) - Cai, Benzhi; Tan, Xueying; Zhang, Yong; Li, Xingda; Wang, Xinyue; Zhu, Jiuxin; Wang, Yang; Yang, Fan; Wang, Baoqiu; Liu, Yanju; Xu, Chaoqian; Pan, Zhenwei; et al.
Abstract : In this study, bone marrow-derived mesenchymal stem cells (BMSCs) were indirectly cocultured with neonatal rat ventricular cardiomyocytes in vitro or intramyocardially transplanted into hypertrophic hearts in vivo. The results showed that isoproterenol-induced typical hypertrophic characteristics of cardiomyocytes were prevented by BMSCs in the coculture model in vitro and after BMSC transplantation in vivo, providing the first evidence for the treatment of myocardial hypertrophy using BMSCs. Abstract: : Bone marrow-derived mesenchymal stem cells (BMSCs) have emerged as a promising therapeutic strategy for cardiovascular disease. However, there is no evidence so far that BMSCs can heal pathological myocardial hypertrophy. In this study, BMSCs were indirectly cocultured with neonatal rat ventricular cardiomyocytes (NRVCs) in vitro or intramyocardially transplanted into hypertrophic hearts in vivo. The results showed that isoproterenol (ISO)-induced typical hypertrophic characteristics of cardiomyocytes were prevented by BMSCs in the coculture model in vitro and after BMSC transplantation in vivo. Furthermore, activation of the Ca 2+ /calcineurin/nuclear factor of activated T cells cytoplasmic 3 (NFATc3) hypertrophic pathway in NRVCs was abrogated in the presence of BMSCs both in vitro and in vivo. Interestingly, inhibition of vascular endothelial growth factor (VEGF) release from BMSCs, but not basic fibroblast growth factor and insulin-like growth factor 1, abolished the protective effects of BMSCs on cardiomyocyte hypertrophy. Consistently, VEGF administration attenuated ISO-induced enlargement of cellular size; the upregulation of atrial natriuretic peptide, brain natriuretic peptide, and β-myosin heavy chain expression; and the activation of Ca 2+ /calcineurin/NFATc3 hypertrophic pathways, and these pathways can be abrogated by blocking VEGFR-1 in cardiomyocytes, indicating that VEGF receptor 1 is involved in the antihypertrophic role of VEGF. We further found that the ample VEGF secretion contributing to the antihypertrophic effects of BMSCs originates from the crosstalk of BMSCs and cardiac cells but not BMSCs or cardiomyocytes alone. Interplay of mesenchymal stem cells with cardiomyocytes produced synergistic effects on VEGF release. In summary, crosstalk between mesenchymal stem cells and cardiomyocytes contributes to the inhibition of myocardial hypertrophy via inhibiting Ca 2+ /calcineurin/NFATc3 hypertrophic pathways in cardiac cells. These results provide the first evidence for the treatment of myocardial hypertrophy using BMSCs. Significance: This study found that mesenchymal stem cells may crosstalk with cardiomyocytes, which causes a synergistic vascular endothelial growth factor (VEGF) release from both kinds of cells and then inhibits pathological cardiac remodeling following hypertrophic stimulation in cardiomyocytes in vitro and in vivo. Blockage of VEGF release from bone marrow-derived mesenchymal stem cells (BMSCs) abolishes the antihypertrophic actions of BMSCs in vitro and in vivo. On the contrary, VEGF administration attenuates hypertrophic signaling of calcineurin/ nuclear factor of activated T cell cytoplasmic 3 signal pathways. This study provides the first evidence for the treatment of myocardial hypertrophy using BMSCs.